The natural product Aristolactam AIIIa as a new ligand targeting the polo-box domain of polo-like kinase 1 potently inhibits cancer cell proliferation - Li Li; Wang Xu; Chen Jing; Ding Hong; Zhang Yu; Hu Tian-cen; Hu Li-hong; Jiang Hua-liang; Shen Xu (Acta Pharmacologica Sinica, 2016)
Aim: To search for novel inhibitors of human polo-like kinase 1 (Plk1), which plays important roles in various aspects of mitotic progression and is believed as a promising anti-cancer drug target, and further investigate the potential inhibition mechanism of active compounds against Plk1, thus developing potent anti-tumor lead compounds. Methods: Surface plasmon resonance (SPR) technology-based assay and enzymatic inhibition assay were used to screen Plk1 inhibitors. Sulphorhodamine B (SRB)-based assay, flow cytometry, confocal microscopy and Western blotting were used to further identify the potent Plk1 inhibitor. To investigate the inhibitory mechanism of the active compound against Plk1, enzymatic inhibition assay, SPR and yeast two-hybrid technology-based assays were used. Results: Aristolactam AIIIa was identified as a new type of Plk1 inhibitors, targeting the Polo Box domain (PBD) which is another efficient tactic for exploring Plk1 inhibitors. Further studies indicated that it could block the proliferations of HeLa, A549, HGC and the HCT-8/V cells (clinical Navelbine-resistant cancer cell), induce mitotic arrest of HeLa cells at G2/M phase with spindle abnormalities and promote apoptosis in HeLa cells. The results from SPR and yeast two-hybrid technology-based assays suggested that it could target both the catalytic domain of Plk1 (CD) and PBD and enhance the CD/PBD interaction. Conclusion: Our current work is expected to shed light on the potential anti-tumor mechanism of Aristolactam AIIIa, and this natural product might be possibly used as a lead compound for further developing anti-tumor drugs.